Accesibilidad del alojamiento turístico emperador ubicado en el Cantón Babahoyo - Ramos Rodriguez, Carlos Luciano (2022)
What are the accessibility conditions of the Emperador tourist accommodation located in the Babahoyo canton? People with physical, visual, auditory, intellectual disabilities, among others, have the right to stay in establishments that offer inclusion, accessibility must be important for service providers, strengthening tourism development, generating greater demands. Hotel establishments offer differences to their competition and preference by tourists with disabilities. In the present case study, the accessibility of the tourist accommodation of the Emperador Hotel located in the Babahoyo canton is analyzed, an observation sheet was made that consists of the collection of data through the visualization of the object of study, it proposes to inspect the location and Using visual data, mark the presence or absence of a service or product, taking as a reference the file of the National Ministry of Tourism Mintur and the INEN 3141 2018-05 standards for gathering information. Through files and interviews, it is analyzed whether or not the Hotel Emperador has an accessible infrastructure and trained personnel for good attention and care of people with disabilities who will be future guests of the establishment.